Leaf Anatomy Profile of Begonia Section Platycentrum Sphenanthera Group From Java and Sumatera, Indonesia - Intani Quarta Lailaty; Muhammad Efendi (UIN Sunan Gunung Djati Bandung, 2023)
Anatomical studies have been used in the classification and identification of Begonia species. However, the research on Indonesian native Begonia is still limited. This study focused to evaluate the importance of leaves’ anatomy character for the identification and classification purpose of the Sphenanthera group in Java and Sumatra. A total of six individuals of four Begonia species used in this study, namely Begonia multangula, B. longifolia, B. pseudoscottii, and B. robusta. This study aimed to describe the anatomical characters of the leaves that are useful in the identification and grouping of Begonia section Platycentrum–Sphenanthera. The anatomical preparations used the paraffin method for the cross-section of leaves and the semi-permanent method for paradermal observations. In general, the epidermal cells of paradermal Begonia leaves are polygonal in shape. Consistently, Begonias have single-type stomata with an anisocytic type which are only present on the abaxial leaves. Begonia Sphenanthera group has a thin cuticle (less than 2 µm), both in the abaxial and adaxial surfaces. The lower epidermis cells are smaller than the upper epidermis cells. The mesophyll is differentiated into palisade and spongy tissue. The number and form of mesophyll tissue are varied, therefore useful for diagnosing an important character in the grouping of Begonias from this section.